问题
I've been experimenting with Codensity
lately which is supposed to relate DList
with []
among other things. Anyway, I've never found code that states this relation. After some experiments I ended up with this:
{-# LANGUAGE RankNTypes #-}
module Codensity where
newtype Codensity f a = Codensity
{ runCodensity :: forall b. (a -> f b) -> f b }
type DList a = Codensity [] [a]
nil :: DList a
nil = Codensity ($ [])
infixr 5 `cons`
cons :: a -> DList a -> DList a
cons x (Codensity xs) = Codensity ($ (xs (x:)))
append :: DList a -> DList a -> DList a
append (Codensity xs) ys = Codensity ($ (xs (++ toList ys)))
toList :: DList a -> [a]
toList xs = runCodensity xs id
fromList :: [a] -> DList a
fromList xs = Codensity (\k -> k xs)
However, the definition of DList
feels a bit icky in my example. Is there a different way to state this relation? Is this even the right way to do this?
回答1:
One view could be that DList
is a way for reordering monoid operations, just as Codensity
is a way for reordering monad operations.
[]
is a free monoid on a
, so let's represent lists using a free writer monad, that is Free ((,) a)
:
module Codensity where
import Control.Monad
import Control.Monad.Free
import Control.Monad.Codensity
import Control.Monad.Trans (lift)
type DList a = Free ((,) a) ()
Now we can define the standard list operations:
nil :: DList a
nil = return ()
singleton :: a -> DList a
singleton x = liftF (x, ())
append :: DList a -> DList a -> DList a
append = (>>)
infixr 5 `snoc`
snoc :: DList a -> a -> DList a
snoc xs x = xs >> singleton x
exec :: Free ((,) a) () -> [a]
exec (Free (x, xs)) = x : exec xs
exec (Pure _) = []
fromList :: [a] -> DList a
fromList = mapM_ singleton
toList :: DList a -> [a]
toList = exec
This representation has the same drawbacks as list when it comes to snoc
. We can verify that
last . toList . foldl snoc nil $ [1..10000]
takes a significant (quadratic) amount of time. However, just as every free monad, it can be improved using Codensity
. We just replace the definition with
type DList a = Codensity (Free ((,) a)) ()
and toList
with
toList = exec . lowerCodensity
Now the same expression is executed instantly, as Codensity
reorders the operations, just like the original difference lists.
回答2:
TL;DR:
DList
for(++)
serves the same purpose asCodensity
for(>>=)
: reassociating the operators to the right.This is beneficial, because for both,
(++)
and(>>=)
, left associated computations (can) exhibit quadratic runtime behaviour.
1. The full story
The plan is as follows:
- We go step by step through an example for
(++)
and(>>=)
, emonstrating the problem with associativity. - We use CPS to avoid quadratic complexity with
DList
andCodensity
- Aftermath and Bonus (Generalize from
(++)
to(<>)
)
2. The problem: quadratic runtime behaviour
2a. List (++)
Keep in mind that while I am using
(++)
as an example, this is valid for other functions as well, if they work analogous to(++)
.
So let's first look at the problem with lists. The concat operation for lists is commonly defined as:
(++) [] ys = ys
(++) (x:xs) ys = x : xs ++ ys
which means that (++)
will always walk the first argument from
start to end. To see when this is a problem consider the following
two computations:
as, bs, cs:: [Int]
rightAssoc :: [Int]
rightAssoc = (as ++ (bs ++ cs))
leftAssoc :: [Int]
leftAssoc = ((as ++ bs) ++ cs)
Let's start with rightAssoc
and walk through the evaluation.
as = [1,2]
bs = [3,4]
cs = [5,6]
rightAssoc = ([1,2] ++ ([3,4] ++ [5,6]))
-- pattern match gives (1:[2]) for first arg
= 1 : ([2] ++ ([3,4] ++ [5,6]))
-- pattern match gives (2:[]) for first arg
= 1 : 2 : ([] ++ ([3,4] ++ [5,6]))
-- first case of (++)
= 1 : 2 : ([3,4] ++ [5,6])
= 1 : 2 : 3 : ([4] ++ [5,6])
= 1 : 2 : 3 : 4 : ([] ++ [5,6])
= 1 : 2 : 3 : 4 : [5,6]
= [1,2,3,4,5,6]
So we have to walk over as
and bs
.
Okay that was not too bad, let's continue to leftAssoc
:
as = [1,2]
bs = [3,4]
cs = [5,6]
leftAssoc = (([1,2] ++ [3,4]) ++ [5,6])
= ((1 : ([2] ++ [3,4])) ++ [5,6])
= ((1 : 2 : ([] ++ [3,4])) ++ [5,6])
= ((1 : 2 : [3,4]) ++ [5,6])
= ([1,2,3,4] ++ [5,6])
-- uh oh
= 1 : ([2,3,4] ++ [5,6])
= 1 : 2 : ([3,4] ++ [5,6])
= 1 : 2 : 3 : ([4] ++ [5,6])
= 1 : 2 : 3 : 4 : ([] ++ [5,6])
= 1 : 2 : 3 : 4 : [5,6]
= [1,2,3,4,5,6]
Uh oh, did you see that we had to walk over as
twice? Once as
[1,2]
and then again inside as ++ bs = [1,2,3,4]
. With each
further operand that is wrongly associated, the list on the left
of (++)
which we have to traverse completely each time will grow
longer in each step, leading to quadratic runtime behaviour.
So as you see above left-associated (++)
will destroy performance.
Which leads us to:
2b. Free monad (>>=)
Keep in mind that while I am using
Free
as an example, this is also the case for other monads, e.g. the instance forTree
behaves like this, too
First, we use the naive Free
type:
data Free f a = Pure a | Free (f (Free f a))
Instead of (++)
, we look at (>>=)
which is defined as and use
(>>=)
in prefix form:
instance Functor f => Monad (Free f) where
return = Pure
(>>=) (Pure a) f = f a
(>>=) (Free m) f = Free ((>>= f) <$> m)
If you compare this with the definition of (++)
from 2a
above, you can
see that the definition of (>>=)
again looks at the first
argument. That raises a first concern, will this perform as bad as in
the (++)
case when associated wrongly? Well, let's see, I use
Identity
here for simplicity but the choice of the functor is not
the important fact here:
-- specialized to 'Free'
liftF :: Functor f => f a -> Free f a
liftF fa = Free (Pure <$> fa)
x :: Free Identity Int
x = liftF (Identity 20) = Free (Identity (Pure 20))
f :: Int -> Free Identity Int
f x = liftF (Identity (x+1)) = Free (Identity (Pure (x+1)))
g :: Int -> Free Identity Int
g x = liftF (Identity (x*2)) = Free (Identity (Pure (x*2)))
rightAssoc :: Free Identity Int
rightAssoc = (x >>= \x -> (f x >>= g))
leftAssoc :: Free Identity Int
leftAssoc = ((x >>= f) >>= g)
We again start with the rightAssoc
variant first:
rightAssoc = (x >>= \x -> (f x >>= g))
~~~
-- definition of x
= ((Free (Identity (Pure 20))) >>= \x -> (f x >>= g))
~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~
-- second case of definition for 'Free's (>>=)
= Free ((>>= \x -> (f x >>= g)) <$> Identity (Pure 20))
~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~
-- (<$>) for Identity
= Free (Identity ((Pure 20) >>= \x -> (f x >>= g)))
~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~
-- first case of the definition for 'Free's (>>=)
= Free (Identity (f 20 >>= g))
~~~~
= Free (Identity ((Free (Identity (Pure 21))) >>= g))
~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~
-- second case of definition for 'Free's (>>=)
= Free (Identity (Free ((>>= g) <$> Identity (Pure 21))))
~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~
= Free (Identity (Free (Identity ((Pure 21) >>= g))))
~~~~~~~~~~~~~~~
= Free (Identity (Free (Identity (g 21))))
~~~~
= Free (Identity (Free (Identity (Free (Identity (Pure 42))))))
Puh, okay I added ~~~~
under the expression that is reduced in the
next step for clarity. If you squint hard enough, you may see some
familiarity from 2a
's' case for rightAssoc
: we walk the two first
arguments (now x
and f
instead of as
and bs
) arguments once.
Without wasting further time, here is leftAssoc
:
leftAssoc = ((x >>= f) >>= g)
~~~
= ((Free (Identity (Pure 20)) >>= f) >>= g)
~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~
= (Free ((>>= f) <$> Identity (Pure 20)) >>= g)
~~~~~~~~~~~~~~~~~~~~~~~~~~~~~
= (Free (Identity ((Pure 20) >>= f)) >>= g)
~~~~~~~~~~~~~~~
= (Free (Identity (f 20)) >>= g)
~~~~
= (Free (Identity (Free (Identity (Pure 21)))) >>= g)
~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~
= Free ((>>= g) <$> (Identity (Free (Identity (Pure 21)))))
~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~
-- uh oh
= Free (Identity (Free (Identity (Pure 21)) >>= g))
~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~
= Free (Identity (Free ((>>= g) <$> Identity (Pure 21))))
~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~
= Free (Identity (Free (Identity ((Pure 21) >>= g))))
~~~~~~~~~~~~~~~~
= Free (Identity (Free (Identity (g 21))))
~~~~
= Free (Identity (Free (Identity (Free (Identity (Pure 42))))))
If you look close, after the uh oh
we have to tear down the
intermediate structure again, just like in the (++)
case (also
marked with uh oh
).
2c. Result so far
In both cases, leftAssoc
leads to quadratic runtime behaviour,
because we rebuild the first argument several times and tear it
down right again for the next operation. This means that at each step
in the evaluation we have to build and tear down a growing
intermediate structure --- bad.
3. The relation between DList
and Codensity
This is where we will discover the relation between DList
and
Codensity
. Each one solves the problem of wrongly associated
computations seen above by using CPS to effectively reassociate to the
right.
3a. DList
First we introduce the definition of DList
and append
:
newtype DList a = DL { unDL :: [a] -> [a] }
append :: DList a -> DList a -> DList a
append xs ys = DL (unDL xs . unDL ys)
fromList :: [a] -> DList a
fromList = DL . (++)
toList :: DList a -> [a]
toList = ($[]) . unDL
and now our old friends:
as,bs,cs :: DList Int
as = fromList [1,2] = DL ([1,2] ++)
bs = fromList [3,4] = DL ([3,4] ++)
cs = fromList [5,6] = DL ([5,6] ++)
rightAssoc :: [Int]
rightAssoc = toList $ as `append` (bs `append` cs)
leftAssoc :: [Int]
leftAssoc = toList $ ((as `append` bs) `append` cs)
Evaluation is roughly as follows:
rightAssoc = toList $ (DL ([1,2] ++)) `append` (bs `append` cs)
= toList $ DL $ unDL (DL ([1,2] ++)) . unDL (bs `append` cs)
~~~~~~~~~~~~~~~~~~~~
= toList $ DL $ ([1,2] ++) . unDL (bs `append` cs)
~~
= toList $ DL $ ([1,2] ++) . unDL ((DL ([3,4] ++)) `append` cs)
~~~~~~~~~~~~~~~~~~~~~~~~~~~
= toList $ DL $ ([1,2] ++) . unDL (DL $ unDL (DL ([3,4] ++)) . unDL cs)
~~~~~~~~~~~~~~~~~~~~
= toList $ DL $ ([1,2] ++) . unDL (DL $ ([3,4] ++) . unDL cs)
~~
= toList $ DL $ ([1,2] ++) . unDL (DL $ ([3,4] ++) . unDL (DL ([5,6] ++)))
= toList $ DL $ ([1,2] ++) . unDL (DL $ ([3,4] ++) . ([5,6] ++))
~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~
= toList $ DL $ ([1,2] ++) . (([3,4] ++) . ([5,6] ++))
~~~~~~
-- definition of toList
= ($[]) . unDL $ DL $ ([1,2] ++) . (([3,4] ++) . ([5,6] ++))
~~~~~~~~~
-- unDL . DL == id
= ($[]) $ (([1,2] ++) . (([3,4] ++) . ([5,6] ++)))
-- move ($[]) to end
= (([1,2] ++) . (([3,4] ++) . ([5,6] ++))) []
-- def: (.) g f x = g (f x)
= (([1,2] ++) ((([3,4] ++) . ([5,6] ++)) []))
= (([1,2] ++) (([3,4] ++) (([5,6] ++) [])))
-- drop unnecessary parens
= (([1,2] ++) (([3,4] ++) ([5,6] ++ [])))
= ([1,2] ++ ([3,4] ++ ([5,6] ++ [])))
~~~~~~~~~~~
-- (xs ++ []) == xs
= ([1,2] ++ ([3,4] ++ ([5,6])))
= (as ++ (bs ++ cs))
Hah! The result is exactly the same as rightAssoc
from 2a
.
Allright, with tension building up, we move on to leftAssoc
:
leftAssoc = toList $ ((as `append` bs) `append` cs)
= toList $ (((DL ([1,2]++)) `append` bs) `append` cs)
= toList $ ((DL (unDL (DL ([1,2]++)) . unDL bs)) `append` cs)
= toList $ ((DL (unDL (DL ([1,2]++)) . unDL (DL ([3,4]++)))) `append` cs)
= toList $ ((DL (([1,2]++) . ([3,4]++))) `append` cs)
= toList $ (DL (unDL (DL (([1,2]++) . ([3,4]++))) . unDL cs))
= toList $ (DL (unDL (DL (([1,2]++) . ([3,4]++))) . unDL (DL ([5,6]++))))
= toList $ (DL ((([1,2]++) . ([3,4]++)) . ([5,6]++)))
= ($[]) . unDL $ (DL ((([1,2]++) . ([3,4]++)) . ([5,6]++)))
= ($[]) ((([1,2]++) . ([3,4]++)) . ([5,6]++))
= ((([1,2]++) . ([3,4]++)) . ([5,6]++)) []
-- expand (f . g) to \x -> f (g x)
= ((\x -> ([1,2]++) (([3,4]++) x)) . ([5,6]++)) []
= ((\x -> ([1,2]++) (([3,4]++) x)) (([5,6]++) []))
-- apply lambda
= ((([1,2]++) (([3,4]++) (([5,6]++) []))))
= ([1,2] ++ ([3,4] ++ [5,6]))
= as',bs',cs' ~ versions of 2a with no prime
= (as' ++ (bs' ++ cs'))
Heureka! The result is associated correctly (to the right), no quadratic slowdown.
3b. Codensity
Okay if you've come to this point you must be seriously interested, that's good,
because so am I :). We start with the definition and Monad
instance of Codensity (with abbreviated names):
newtype Codensity m a = C { run :: forall b. (a -> m b) -> m b }
instance Monad (Codensity f) where
return x = C (\k -> k x)
m >>= k = C (\c -> run m (\a -> run (k a) c))
-- hidden as a instance for `MonadTrans`
liftCodensity :: Monad m => m a -> Codensity m a
liftCodensity m = C (m >>=)
lowerCodensity :: Monad m => Codensity m a -> m a
lowerCodensity a = run a return
I guess you know what comes next:
x :: Codensity (Free Identity) Int
x = liftCodensity (Free (Identity (Pure 20)))
= C (Free (Identity (Pure 20)) >>=)
-- note the similarity to (DL (as ++))
-- with DL ~ Codensity and (++) ~ (>>=) !
f :: Int -> Codensity (Free Identity) Int
f x = liftCodensity (Free (Identity (Pure (x+1))))
= C (Free (Identity (Pure (x+1))) >>=)
g :: Int -> Codensity (Free Identity) Int
g x = liftCodensity (Free (Identity (Pure (x*2))))
= C (Free (Identity (Pure (x*2))) >>=)
rightAssoc :: Free Identity Int
rightAssoc = lowerCodensity (x >>= \x -> (f x >>= g))
leftAssoc :: Free Identity Int
leftAssoc = lowerCodensity ((x >>= f) >>= g)
Before we go through the evaluation once again, you might be
interested in the comparison of append
from DList
and (>>=)
from
Codensity
(unDL
~
run
), go ahead and do that if you
want, I'll wait for you.
Okay we start with rightAssoc
:
rightAssoc = lowerCodensity (x >>= \x -> (f x >>= g))
~~~
-- def of x
= lowerCodensity ((C (Free (Identity (Pure 20)) >>=)) >>= \x -> (f x >>= g))
-- (>>=) of codensity
= lowerCodensity (C (\c -> run (C (Free (Identity (Pure 20)) >>=)) (\a -> run ((\x -> (f x >>= g)) a) c)))
-- run . C == id
= lowerCodensity (C (\c -> Free (Identity (Pure 20)) >>= \a -> run ((\x -> (f x >>= g)) a) c))
-- substitute x' for 'Free (Identity (Pure 20))' (same as only x from 2b)
= lowerCodensity (C (\c -> x' >>= \a -> run ((\x -> (f x >>= g)) a) c))
~~~
= lowerCodensity (C (\c -> x' >>= \a -> run ((\x -> (C (Free (Identity (Pure (x+1))) >>=)) >>= g) a) c))
~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~
= lowerCodensity (C (\c -> x' >>= \a -> run ((\x -> (C (\c2 -> run (C (Free (Identity (Pure (x+1))) >>=)) (\a2 -> run (g a2) c2)))) a) c))
~~~~~~
= lowerCodensity (C (\c -> x' >>= \a -> run ((\x -> (C (\c2 -> (Free (Identity (Pure (x+1))) >>=) (\a2 -> run (g a2) c2)))) a) c))
-- again, substitute f' for '\x -> Free (Identity (Pure (x+1)))' (same as only f from 2b)
= lowerCodensity (C (\c -> x' >>= \a -> run ((\x -> (C (\c2 -> (f' x >>=) (\a2 -> run (g a2) c2)))) a) c))
~~~~
= lowerCodensity (C (\c -> x' >>= \a -> run ((\x -> (C (\c2 -> (f' x >>=) (\a2 -> run (C (Free (Identity (Pure (a2*2))) >>=)) c2)))) a) c))
~~~~~~
= lowerCodensity (C (\c -> x' >>= \a -> run ((\x -> (C (\c2 -> (f' x >>=) (\a2 -> (Free (Identity (Pure (a2*2))) >>=) c2)))) a) c))
-- one last time, substitute g' (g from 2b)
= lowerCodensity (C (\c -> x' >>= \a -> run ((\x -> (C (\c2 -> (f' x >>=) (\a2 -> (g' a2 >>=) c2)))) a) c))
-- def of lowerCodensity
= run (C (\c -> x' >>= \a -> run ((\x -> (C (\c2 -> (f' x >>=) (\a2 -> (g' a2 >>=) c2)))) a) c)) return
= (\c -> x' >>= \a -> run ((\x -> (C (\c2 -> (f' x >>=) (\a2 -> (g' a2 >>=) c2)))) a) c) return
= (x' >>= \a -> run ((\x -> (C (\c2 -> (f' x >>=) (\a2 -> (g' a2 >>=) c2)))) a) return)
~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~
= (x' >>= \a -> run (C (\c2 -> (f' a >>=) (\a2 -> (g' a2 >>=) c2))) return)
~~~~~~
= (x' >>= \a -> (\c2 -> (f' a >>=) (\a2 -> (g' a2 >>=) c2)) return)
~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~
= (x' >>= \a -> (f' a >>=) (\a2 -> g' a2 >>= return))
-- m >>= return ~ m
= (x' >>= \a -> (f' a >>=) (\a2 -> g' a2))
-- m >>= (\x -> f x) ~ m >>= f
= (x' >>= \a -> (f' a >>= g'))
-- rename a to x
= (x' >>= \x -> (f' x >>= g'))
And we can now see that the (>>=)
s are associated to the right, this
is not yet particularly astonishing, given that this was also the case
at the start. So, full of anticipation, we turn our attention to our
last and final evaluation trace, leftAssoc
:
leftAssoc = lowerCodensity ((x >>= f) >>= g)
-- def of x
= lowerCodensity ((C (Free (Identity (Pure 20)) >>=) >>= f) >>= g)
-- (>>=) from Codensity
= lowerCodensity ((C (\c -> run (C (Free (Identity (Pure 20)) >>=)) (\a -> run (f a) c))) >>= g)
~~~~~~
= lowerCodensity ((C (\c -> (Free (Identity (Pure 20)) >>=) (\a -> run (f a) c))) >>= g)
-- subst x'
= lowerCodensity ((C (\c -> (x' >>=) (\a -> run (f a) c))) >>= g)
-- def of f
= lowerCodensity ((C (\c -> (x' >>=) (\a -> run (C (Free (Identity (Pure (a+1))) >>=)) c))) >>= g)
~~~~~~
= lowerCodensity ((C (\c -> (x' >>=) (\a -> (Free (Identity (Pure (a+1))) >>=) c))) >>= g)
-- subst f'
= lowerCodensity ((C (\c -> (x' >>=) (\a -> (f' a >>=) c))) >>= g)
~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~
= lowerCodensity (C (\c2 -> run (C (\c -> (x' >>=) (\a -> (f' a >>=) c))) (\a2 -> run (g a2) c2)))
~~~~~~
= lowerCodensity (C (\c2 -> (\c -> (x' >>=) (\a -> (f' a >>=) c)) (\a2 -> run (g a2) c2)))
-- def of g
= lowerCodensity (C (\c2 -> (\c -> (x' >>=) (\a -> (f' a >>=) c)) (\a2 -> run (C (Free (Identity (Pure (a2*2))) >>=)) c2)))
~~~~~~
= lowerCodensity (C (\c2 -> (\c -> (x' >>=) (\a -> (f' a >>=) c)) (\a2 -> (Free (Identity (Pure (a2*2))) >>=) c2)))
-- subst g'
= lowerCodensity (C (\c2 -> (\c -> (x' >>=) (\a -> (f' a >>=) c)) (\a2 -> (g' a2 >>=) c2)))
-- def lowerCodensity
= run (C (\c2 -> (\c -> (x' >>=) (\a -> (f' a >>=) c)) (\a2 -> (g' a2 >>=) c2))) return
= (\c2 -> (\c -> (x' >>=) (\a -> (f' a >>=) c)) (\a2 -> (g' a2 >>=) c2)) return
= ((\c -> (x' >>=) (\a -> (f' a >>=) c)) (\a2 -> g' a2 >>= return))
= ((\c -> (x' >>=) (\a -> (f' a >>=) c)) (\a2 -> g' a2))
= ((\c -> (x' >>=) (\a -> (f' a >>=) c)) g')
= (x' >>=) (\a -> (f' a >>=) g')
= (x' >>=) (\a -> (f' a >>= g')
= (x' >>= (\a -> (f' a >>= g'))
= (x' >>= (\x -> (f' x >>= g'))
Finally there we have it, all binds associated to the right, just how we like them!
4. Aftermath
If you made it until here, congratulations. Let's summarize what we did:
- We demonstrated the problem with wrongly associated
(++)
in2a
and(>>=)
in2b
- We've shown the solution using
DList
in3a
andCodensity
in3b
. - Demonstrated the power of equational reasoning in Haskell :)
5. Bonus
Actuall, we can generalize DList
from (++)
and use (<>)
instead
to get DMonoid
, reordering (<>)
.
newtype DMonoid m = DM { unDM :: m -> m }
instance Monoid m => Monoid (DMonoid m) where
mempty = DM (mempty <>)
x `mappend` y = DM (unDM x . unDM y)
liftDM :: Monoid m => m -> DMonoid m
liftDM = DM . (<>)
lowerDM :: Monoid m => DMonoid m -> m
lowerDM = ($ mempty) . unDM
Then the comparison goes as follows:
DMonoid
is a (my invention) "monoid transformer", reassociating(<>)
to the rightCodensity
is a monad transformer, reassociating(>>=)
to the right
来源:https://stackoverflow.com/questions/32191851/relation-between-dlist-and-with-codensity